Activities of the Lithuanian Mathematical Society in 2021–2024 - Štikonas, Artūras (Lietuvos matematikos rinkinys, 2024)
The article gives a survey of mathematical life and activities of the Lithuanian Mathematical Society during the past three years.
Keywords: mathematical activities in Lithuania; Lithuanian Mathematical Society; participation in international organizations